THE CONCEPT OF INDONESIA’S AEROTROPOLIS DEVELOPMENT IN WEST JAVA KERTAJATI - Luh Putu Widyaningsih, Ni; Julianesyah Putri, Agnes; Listya Cahya, Darmawan; Sinaga, Obsatar (International Journal of Psychosocial Rehabilitation, 2020)
The development of airports in Indonesia is seen from the service and security aspects, at present the airport services have not been maximized because they have exceeded capacity due to the lack of operational supporting facilities and the development of passenger improvement. The development of Soekarno-Hatta International Airport has exceeded passenger capacity and Husein Sastranegara Airport is still used as a support for military defense. The purpose of this study is to identify the factors that influence the development of the Aerotropolis concept in Kertajati and develop a model of Aerotropolis concept development that is suitable for development in Kertajati, West Java. This research method was carried out using a descriptive qualitative research method. The results of this study indicate that the factors that influence the development of the Aerotropolis concept in Kertajati are topography, land slope, land use, are not prone to disasters and have accessibility to get to the region. The Aerotropolis concept development model in Kertajati uses design schematics and related theories about Aerotropolis from John D. Kasarda. The concept of Kertajati Aerotropolis as meeting the needs of non-aviation areas which is also a supporter of Kertajati Airport activities as the center of the city. Suggestion from the research that has been done is that the development of the Aerotropolis area must be carried out in order to become an economic driver in the region because there are several non-flight activities and it is necessary to conduct further studies and studies on airports and urban areas as the center of the development of the Aerotropolis area.